2011
DOI: 10.1007/s10334-011-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal stress on 1H NMR-based metabolic profiling of rat amniotic fluid

Abstract: Some consistent metabolic changes, observable by (1)H NMR spectroscopy, occurred in amniotic fluid during prenatal stress caused by hyperthermia and LPS-induced inflammation and had an impact on the gestation outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A decrease in maternal circulating glucose concentrations likely results in decreased fetal uptake of glucose, possibly having long-lasting effects on postnatal responses (Battaglia and Meschia, 1978). Indeed, a study in rats reported a decrease in glucose in the amniotic fluid 2 h following LPS administration on gestational d 19 (Serriere et al, 2011). As stated by Battaglia and Meschia (1978), hypoglycemia in the dam results in hypoglycemia in the fetus, altering the glucose requirements of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in maternal circulating glucose concentrations likely results in decreased fetal uptake of glucose, possibly having long-lasting effects on postnatal responses (Battaglia and Meschia, 1978). Indeed, a study in rats reported a decrease in glucose in the amniotic fluid 2 h following LPS administration on gestational d 19 (Serriere et al, 2011). As stated by Battaglia and Meschia (1978), hypoglycemia in the dam results in hypoglycemia in the fetus, altering the glucose requirements of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…The AF metabolome has been frequently studied using NMR in clinical and preclinical studies, , but for the past few years, the use of LC–MS is quickly increasing . Several studies already report the use of different solvents such as MeOH or ACN to deproteinize and extract metabolites ,, but without a rationale for their choice.…”
Section: Resultsmentioning
confidence: 99%